Targeted Temperature Management Post-Cardiac Arrest: Shifting Paradigms from Hypothermia to Strict Normothermia and its Impact on Neurological Prognostication - Kowalewski, Piotr; Kuchta, Eliza; Kowalczyk, Natalia; Wrzosek, Kacper; Dudek, Karolina; Błażukiewicz, Jan; Ciupak, Klaudia; Garbacki, Klaudiusz; Popek, Lena; Dudek, Bartosz; et al. (Quality in Sport, 2026)
Background. Cardiac arrest (CA) remains a major global health challenge with high risk of severe neurological impairment. Post-cardiac arrest syndrome (PCAS), particularly hypoxic-ischemic brain injury, drives mortality and long-term disability. Targeted temperature management (TTM), traditionally a neuroprotective cornerstone, is currently being re-evaluated. Aim. To analyze current evidence on post-CA temperature management, focusing on the shift from therapeutic hypothermia to strict normothermia and its implications for neurological prognostication. Materials and methods. This narrative review synthesizes 30 peer-reviewed publications, including randomized trials, systematic reviews, and international guidelines (ERC, ESICM, NCS). It evaluates PCAS pathophysiology, hypothermia versus normothermia outcomes, technical TTM implementation, and multimodal neuroprognostication. Results. Recent high-quality evidence shows no significant benefit of routine therapeutic hypothermia (32–34°C) over strict normothermia in improving survival or neurological outcomes. Guidelines now emphasize active fever prevention (≤37.5°C) using precise control systems. While TTM modulates systemic inflammation (e.g., IL-6), this does not independently lower mortality. Neurological prognostication requires a delayed, multimodal approach integrating clinical assessments and biomarkers like neuron-specific enolase (NSE), while accounting for confounders. Conclusions. Post-CA management has shifted toward individualized, precision-based care, with strict normothermia and active fever prevention as the recommended standard. Accurate neuroprognostication necessitates adherence to guideline-directed timing and multimodal strategies. Future research should identify specific subgroups benefiting from hypothermia and develop adjunctive therapies.